An Association Between Glatiramer Acetate and Malignant Melanoma. Issue 7 (September 2016) - Walker, John; Smylie, AnneLiese; Smylie, Michael
Abstract : A 43-year-old female receiving immunomodulatory therapy with glatiramer acetate (copaxone, GA) for relapsing, remitting multiple sclerosis was diagnosed with stage IIIB melanoma that recurred <7 months after resection and lymphadenectomy. In preparation for systemic therapy the patient discontinued GA, and shortly thereafter experienced spontaneous and complete clinical and radiographic resolution of her disease. The development and subsequent regression of melanoma in this patient may be due to the use and subsequent discontinuation of GA, and our discussion of the case includes the potential immunologic mechanisms that may provide an explanation for our findings. To the best of our knowledge, this case represents the first reported association between the immunomodulatory agent GA and malignant melanoma.